Antecedents and outcomes of migrant workers' sociocultural adjustment in the hospitality industry. (September 2016) - Kim, Woo Gon; Choi, Hyung-Min; Li, Jun (Justin)
Abstract: Migrant workers are an important part of the labor force for the hospitality industry in developed countries and emerging markets. The purpose of this study is to investigate the relationship between perceived organizational support (POS) and dominant cultural orientation (DCO), sociocultural adjustment (SCA), job satisfaction (JS), life satisfaction (LS), and turnover intention (TI) of migrant workers. This research uses a respondent-driven sampling (RDS) method with a dual incentive system to attain hard-to-reach migrant employees. The findings demonstrate that both POS and DCO have a significant and positive relationship with SCA and, interestingly, that POS has a stronger impact on hospitality migrants' SCA than DCO. The findings also imply that although personal efforts of migrant workers are important for their effective socialization, positive support from a hospitality organization plays a far more important role. Furthermore, this study highlights the significant relationships between POS and JS and between DCO and LS. The findings also show that SCA had a significant and positive effect on LS and that hospitality migrants who adjust well in their host society tend to have a high satisfaction with their lives in the foreign country and are apt to stay longer in their positions.